Online Community Based Marketing Strategy: The Key to Building Long-Term Loyalty - Gunawan (Journal of Management, 2022)
This study aims to describe and analyze how online community-based marketing strategies are implemented by companies to build long-term customer loyalty. In the context of technological advancement and digitalization, online communities have become an important medium for strengthening the relationship between brands and consumers. The approach used in this research is a qualitative descriptive method, with data collection techniques including in-depth interviews, participatory observation, and documentation studies of several online communities that actively support specific brands. The results of the study indicate that digital community-based marketing strategies are effective in fostering long-term customer loyalty. Through active and meaningful interactions within online communities, customers feel more connected and develop a sense of ownership toward the brand. The provision of relevant content, prompt responses to feedback, reward programs, and involvement in community events are key factors that enhance customer engagement. Additionally, the use of data analytics helps companies tailor marketing strategies to customer needs, thereby strengthening relationships and encouraging customers to become brand advocates.